CSU professor wins top philosophy prize - Kalaaji, Rahaf, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 2003)
Holmes Rolston is recognized as the founder of environmental ethics, a prolific thinker who brought religion and nature together in unprecedented ways. He has found CSU a stimulating environment, but is still surprised at being invited to Buckingham Palace. The Templeton Prize, given by Prince Philip, is perhaps the top honor a CSU faculty member has ever received.
Keywords: philosophy professor; Colorado State University; Templeton Prize; Rolston, Holmes, 1932-2025